Bioinformatics of Metabolomics in Diabetes Mellitus Type 2 - Taha El-Lethy Abou-Sree; Ahmad Sliem Hamdy (Journal of Bioinformatics And Diabetes, 2014)
Diabetes mellitus type 2 (DMT2) is a complex polygenic disorder. DMT2 is a result of insulin resistance and destruction of pancreatic β-cell or dysfunction. Therefore, glucose builds up in the bloodstream, leading to nerve damage, blindness, organ failures and sometimes death. Recently, some recently discovered genes play a key role in regulating the sensitivity to insulin. Scientists have long known that the disease often runs in families, and other genetic links. Human genetic discoveries will keep improving our knowledge about diabetes for many years to come. Varieties of prospective diabetic researches were developed to diagnose and control DMT2. Researchers spent thousands of millions of dollars to address DMT2. Pioneers of advanced biotechnology developed bioinformatics tools that changed the course of research about the role of metabolomics in DMT2. It will facilitate the identification of possible causes of DMT2 in genome studies. The present article aimed at reviewing the research studies per training to metabolomics and bioinformatics in genome studies in relation to DMT2.
Keywords: Bioinformatics